Dysfunction of Pre-Attentive Visual Information Processing in Drug-Naïve Women, But Not Men, During the Initial Episode of Major Depressive Disorder - Yang, Xiuxian; Wang, Qihe; Qiao, Zhengxue; Qiu, Xiaohui; Han, Dong; Zhu, Xiongzhao; Zhang, Congpei; Yang, Yanjie (Frontiers in Psychiatry, 2020)
Women are twice as likely as men to develop depression. Few studies have explored gender difference in cognitive function of patients with MDD. The gender difference in the pre-attentive information processing of MDD patients is still poorly understood. To examine the gender differences in change detection, 30 medication-free MDD patients (15 women) and 30 Age and education matched controls (15 women) were recruited. The deviant-standard reverse oddball paradigm (50 ms/150 ms) was used to obtain the visual mismatch negativity (vMMN) in first episode MDD patients. Compared to men with MDD, women with MDD showed a significantly decreased increment vMMN, while there was no gender difference in decrement vMMN. The increment vMMN amplitude in MDD women was smaller than in healthy women, whereas there was no difference in decrement vMMN. Neither increment nor decrement vMMN differed between MDD men and healthy men. The mean amplitude of increment vMMN was not correlated with symptoms of MDD in MDD patients and MDD women. To conclude, MDD women had a dysfunction of visual information processing at pre-attentive stage.